2014
DOI: 10.1080/00207217.2014.966779
|View full text |Cite
|
Sign up to set email alerts
|

Accurate FDTD modelling for dispersive media using rational function and particle swarm optimisation

Abstract: This article presents an accurate finite-difference time domain (FDTD) dispersive modelling suitable for complex dispersive media. A quadratic complex rational function (QCRF) is used to characterise their dispersive relations. To obtain accurate coefficients of QCRF, in this work, we use an analytical approach and a particle swarm optimisation (PSO) simultaneously. In specific, an analytical approach is used to obtain the QCRF matrix-solving equation and PSO is applied to adjust a weighting function of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…First, we consider human blood from 300 MHz to 3 GHz. The modified Lorentz parameters are extracted by using the particle swarm optimization [29,30] for the complex relative permittivity data [31]. They are 0 = 6.9379 ⋅ 10 21 , 1 = 1.5057 ⋅ 10 12 , 0 = 6.1637 ⋅ 10 18 , 1 = 4.5425 ⋅ 10 10 , 2 = 1, and ,∞ = 31.1662.…”
Section: Resultsmentioning
confidence: 99%
“…First, we consider human blood from 300 MHz to 3 GHz. The modified Lorentz parameters are extracted by using the particle swarm optimization [29,30] for the complex relative permittivity data [31]. They are 0 = 6.9379 ⋅ 10 21 , 1 = 1.5057 ⋅ 10 12 , 0 = 6.1637 ⋅ 10 18 , 1 = 4.5425 ⋅ 10 10 , 2 = 1, and ,∞ = 31.1662.…”
Section: Resultsmentioning
confidence: 99%
“…were challenging due to the difficulty of developing a time domain dispersion model for them. Recently, the present authors have demonstrated a quadratic complex rational function (QCRF) model [19,20] for photovoltaic materials [21,22], thus in this work, we employ QCRF based FDTD method for a full-wave optical simulation (400 ~ 1200 nm) of perovskite/silicon tandem cells. To simulate a wafer-based c-Si in FDTD, we measure the absorption of a 2 micron-thick c-Si cell within a tandem cell, and then analytically extend to a larger thickness in the following manner.…”
Section: Theorymentioning
confidence: 99%
“…In order to accurately model the behavior of the materials used in the experiments (such as c-Si and silver), a recently developed time-domain dispersion model, called quadratic complex rational function (QCRF), is used [25,33]. Other experimental materials of interest (e.g., ZnO and ITO) were assumed to be non-dispersive and non-absorptive, since thin ITO and ZnO layers generally appear transparent in the visible wavelengths and their single path absorption of 70 nm ITO does not exceed 2.42% for near-infrared wavelengths below 1000 nm.…”
Section: Parasitic Absorption Modelingmentioning
confidence: 99%